Influence of Nostoc muscorum on microbial activity and soil aggregation - PALMA, R M; CAIRE, G ZULPA DE; ZACCARO, M C; CANO, M STORNI DE (The Indian Journal of Agricultural Sciences, 2013)
The effect of sodic soil of exopolysaccharide isolated from Nostoc muscorum or the addition of a cyanobacterial massproliferation were evaluated in a greenhouse experiment. To establish the effect of biomass and exopolysaccharide on thestructure, oxidizable carbon and soluble carbon contents and microbial activity of the soil, two treatments were carriedout (inoculations with biomass and exopolysaccharide). N. muscorum mass and exopolysaccharide application to thesoil promotes aggregation and aggregate stability along 2 years of treatment. The slow organic C build-up due to thesetreatments may have resulted from the high microbial activity assessed. The exopolysaccharide application was moreeffective for macroaggregates (